Importance of Intrinsic and Instrumental Value of Education in Pakistan (Journal of Education and Educational Development, 2020)
Normally, effectiveness of any object or thing is judged by two values; intrinsic and instrumental. To compare intrinsic value of education with instrumental value, this study has used the following variables: getting knowledge for its own sake, getting knowledge for social status, getting knowledge for job or business endeavor and getting knowledge for both purposes, which is for its own sake and also for job, business or status. For this research quantitative method was used and a questionnaire was deployed to collect responses from 465 bachelor degree students from all over Pakistan (combining all provinces including Gilgit & AJK). It was found that the students gave mixed responses of acknowledging both values of education during the survey. The research has significant relationship between each of its independent and dependent variables, although the strength of those relationships was weak in nature. However, 60% of the respondents when asked whether they will get their first or bachelor’s degree even if there is no instrumental value attached with it, responded in affirmative. This concludes that bachelor degree students in Pakistan give more value to intrinsic nature of education than its instrumental value.